Distribution of inorganic and organic contaminants in sediments from Sydney Olympic Park and the surrounding Sydney metropolitan area - Ying, G.; Rawson, Christopher; Kookana, R.; Warne, M.; Peng, P.; Li, X.; Laginestra, E.; Tremblay, L.; Chapman, J.; Lim, R. (Royal Society of Chemistry, 2009)
Organic and inorganic contamination was assessed for sediments from wetlands and water bodies within the Sydney Olympic Park (SOP, remediated sites) and its surroundings (unremediated sites) and urban reference sites in the Sydney Basin. Among the seven elements analysed (As, Cd, Cr, Cu, Pb, Ni and Zn), Zn concentrations were the highest, followed by Pb, Cu and Cr in the sediments of SOP. Significantly higher concentrations (p < 0.05) of DDTs were found in sediments of the Homebush Bay and Parramatta River sites compared with the urban reference sites, mainly due to past manufacturing of DDT in the Homebush Bay area. However, no significant differences (p > 0.05) in concentrationswere found for polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) as well as DDTs between sediments from SOP and the urban reference sites. Source indicators suggest that PAHs in the sediments originated from combustion processes. Two distinct groups of dioxin profiles were observed within SOP and its surroundings. Levels of dioxins were more than 100 pg WHO-TEQ/g dry weight of sediment at five sites adjacent to the SOP boundaries. Based on the findings of the chemical profiles of the contaminants, the remediated sites in SOP can be regarded as similar to the urban reference sites within the Sydney Basin, while the adjacent unremediated sites have higher concentrations, especially of dioxins, that could still affect organisms in the aquatic environment.